Korelasi Penguasaan Materi Dasar Dan Kemampuan Komunikasi Terhadap Prestasi Belajar Matematika Siswa Kelas X Di Sma Negeri 2 Rembang Tahun 2015/2016Penelitian Korelasi Kelas X Semester Genap Di SMA Negeri 2 Rembang Tahun Ajaran 2015/2016 - Chandra, Evie Noviyana, Dra. Sri Sutarni (2016)
The aim of research to describe and analyze: (1) the effect of mastery of the material base of the students on the learning achievement, (2) the effect of mathematical communication skills to learning achievement, (3) the interaction between mastery of basic materials and communication skills to learning achievement. This type of research is based on a quantitative approach. Design of this study is correlational. The study population was all class X SMA N 2 Rembang the second semester of the 2015/2016 academic year. The study sample consisted of two classes. The sampling technique using cluster random sampling. The test method usage data collection and documentation. Data were analyzed using multiple linear regression. The results of the data analysis with a significance level of 5% was obtained: (1) no significant effect on learning achievement mastery of mathematics, with a value of t = 4.389> table = 2.00 (t test) (2) there was a significant influence on the communication skills mathematics learning achievement, with a value of t = 3.354> table = 2.00 (t test) (3) no significant effect ABILITY mastery of basic materials and communication on the learning achievement with a value of F = 14.030> F table = 3.16 (F test ).